Ultrasound and Cystic Echinococcosis - Brunetti, Enrico; Tamarozzi, Francesca; Macpherson, Calum; Filice, Carlo; Piontek, Markus Schindler; Kabaalioglu, Adnan; Dong, Yi; Atkinson, Nathan; Richter, Joachim; Schreiber-Dietrich, Dagmar; Dietrich, Christoph F (Ultrasound International Open, 2018)
The introduction of imaging techniques in clinical practice 40 years ago changed the clinical management of many diseases, including cystic echinococcosis (CE). For the first time cysts were clearly seen before surgery. Among the available imaging techniques, ultrasound (US) has unique properties that can be used to study and manage cystic echinococcosis. It is harmless, can image almost all organs and systems, can be repeated as often as required, is portable, requires no patient preparation, is relatively inexpensive and guides diagnosis, treatment and follow-up without radiation exposure and harm to the patient. US is the only imaging technique which can be used in field settings to assess CE prevalence because it can be run even on solar power or a small generator in remote field locations. Thanks to US classifications, the concept of stage-specific treatments was introduced and because US is repeatable, the scientific community has gained a clearer understanding of the natural history of the disease. This paper reviews the scope of US in CE, describes its strengths and weaknesses compared to other imaging techniques and its relationship with serodiagnosis and discusses sonographic features that may be helpful in differential diagnosis.
Keywords: puncture– aspiration–injection–re-aspiration (PAIR); liver cysts; albendazole; guidelines